Nutrition and Specific Diseases by Women during the Life Course - Zyriax, Birgit‐Christiane; Makarova, Nataliya (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The prevalence rates of risk factors for premature mortality and early non-communicable diseases are growing due to the increasing prevalence of poor nutrition habits, increasing levels of stress, and sedentary lifestyles. The life course epidemiology offers an integrative approach which guides research on health, human development, and ageing. The translation of this life course approach to women's health is indispensable. It comprises the investigation of risk factors across the life that influence the timing of menarche, fertility, pregnancy outcomes, gynaecological disorders, and age at menopause. It also recognises the important influence of reproductive health on later non-communicable disease risks. The continuity of reproductive health and the relationship between different biomarkers and risk factors are taken into account in this integrative approach. Within women's life courses, lifestyle plays an essential role, ranging from young age to pregnancy, menopause, and healthy aging. The underlying mechanisms and the effect sizes between nutrition and many diseases are only partly known due to the often multifactorial disease processes. The link between lifestyle and the growing rates of different diseases (e.g., cervical, ovarian carcinoma, breast cancer, cardiovascular diseases, or diabetes mellitus) needs to be investigated further. New scientific approaches are being used to try to relate individual biomarkers to dietary patterns and changes in the microbiome in order to make risk potentials visible earlier. The collection of scientific contributions on nutrition and women's health is presented here.